Experimental parameter identification for elastocaloric air cooling. (April 2019) - Michaelis, Nicolas; Welsch, Felix; Kirsch, Susanne-Marie; Schmidt, Marvin; Seelecke, Stefan; Schütze, Andreas
Highlights: Novel approach for experimental determination of SMA latent heat in ferroic cooling. Estimated air temperature change ∆T achieved by adiabatic cycling of SMA wires. Comparison of experimental determination of HTC with Churchill-Bernstein equation. Heat transfer coefficient (HTC) for SMA wire in varying airflow rates up to 5 m s −1 . Abstract: This contribution provides an experimental analysis of relevant parameters to determine the air cooling potential of elastocaloric shape memory alloys (SMAs) in the form of wires. An essential step consists in developing a scientific test setup, which offers the ability to determine these parameters under varying conditions like wire geometry, material composition, and process parameters. With the help of this test setup the influence of different airflow rates on the heat transfer from SMA wire to air and the coherent heat transfer coefficients as well as the approximate air temperature ΔT values are determined and presented in this contribution. Furthermore, the latent heat of the SMA material is experimentally identified with a novel approach based on comparing dynamic temperature changes achieved by elastocaloric phase transformation with direct caloric heating. Analysing these parameters will greatly support the simulation, development and construction of elastocaloric air cooling devices to provide environmentally friendly alternatives to the prevalent vapour compression based cooling principles.